Poder e território: uma avaliação dos padrões de competição política no Estado do Pará - SOUZA, Carlos Augusto da Silva (Universidade Federal de Juiz de Fora, 2021)
To examine the patterns of electoral competition observed in the State of Pará, based on a geographical analysis that contemplates the county as a privileged scenario of the political game, is the purpose of this paper. The approach adopted seeks to understand the functioning of the political system that develops in the legislative elections for the Lower House, from the effects produced by the rules that guide the electoral process. With this, the intention is to try to identify the existence of some territorial pattern that guides the actions of the deputies in the construction of their electoral bases.